The ′reading man flap′ for pressure sore reconstruction - Stamatis Sapountzis; Hyoung Joon Park; Ji Hoon Kim; Achilleas Chantes; Rong Min Beak; Chan Yeong Heo (Indian Journal of Plastic Surgery, 2011)
Background: The treatment of pressure sores represents a significant challenge to health care professionals. Although, pressure wound management demands a multidisciplinary approach, soft tissue defects requiring reconstruction are often considered for surgical management. Myocutaneous and fasciocutaneous flaps can provide stable coverage of pressure sores. Purpose: Here, we describe our experience using a recent fasciocutaneous flap, which is named ′reading man′ flap, in sacral, ischial, and trochanteric pressure sores. Materials and Methods: During a period of 1 year the authors operated 16 patients, 11 men, and 5 women, using the reading man flap. The ages of the patients ranged from 24 to 78 years. The location of pressure sores was 8 sacral, 5 ischial, and 3 trochanteric pressure sores. The mean size of pressure sores was 8 cm × 9 cm. Results: All pressure sores covered bt the Reading Man flap healed asymptomatically. After follow-up of 2-8 months, no recurrences were encountered and no further surgical intervention was required. Conclusion: The reading man flap was found to be a useful technique for the closure of pressure sore in different anatomic locations. The advantage of tension-free closure and the minimal additional healthy skin excision made this flap a useful tool in pressure sore reconstructions.